Building Smarter Infrastructure:: Resource Productivity in a Residential Development for Steinhatchee, Florida - LUONI, Stephen (ARCC Conference Repository, 2019)
Environmental reforms in America have developed a significant repertoire of conservation practices directly proportional to the boom in suburban development since World War II. The chief obstacle to past comprehensive reforms in land development has been the fragmented approach of individual conservation practices, as their particular science and application were developed independently of one another. The following is a case study in design for The Conservancy, a "green development” for a 56-unit rural residential community on the Gulf of Mexico. The goal of design and research is to recombine environmental technologies in planning, infrastructure, landscape architecture, and architecture towards more integrated community development. Design methodologies are implemented to address three conservation criteria common to all green economy business models. First is advanced resource productivity to ease the energy economy's reliance on nonrenewable resources. Infrastructural logics, otherwise isolated in conventional development, are bundled into a mosaic with new operational overlaps. Second is the creation of closed-loop energy systems that promote the recycling of energy and materials to eliminate waste. Building and site utility systems are modeled after "feedback” in biological systems. Third is the responsible stewardship of existing resources that harness the ecology to create sustainable land use configurations. Landscape and architecture are integrated into a unified planning module as biological systems serve urbanizing functions. Since the lack of integrative thinking has been the obstacle to sustainable land development, recombinant design modalities, such as those used in The Conservancy, rather than technological innovation, will play the more critical role in developing sustainable environments.